URBAN NARRATIVES: A VIDEO-LETTER PROCESS WITH THE NEWSPAPER BOCA DE RUA - Bechler, Janaina; Sousa, Edson Luiz André (Revista Conhecimento Online: Diversidade e Inclusão Social, 2020)
ABSTRACT The present study shares the process of the collective achievement of a video-letter regarding the city of Porto Alegre, made with a group of directors of the Boca de Rua (Street Mouthpiece) newspaper, which is made by the homeless people of Porto Alegre. It highlights a perspective that sees in the narrator of the city its expression, and bets that there is sharing and sociability stemming from the fragments of narratives produced by the multiplicities that compose it. As a basis, it introduces some concepts of narrative and self-narrative, assuming, based on psychoanalytic theory, that the “I” is eccentric to the subject, and that the self exists as a partial construction. Through the authors W. Benjamin, P. Ricoeur, J-M. Gagnebin, J. Butler e J. Lacan, it points out the importance of composing narratives in the assembly of oneself and the city, creating connections when appropriate, or even legitimizing the fragmentary character of the narrative. The article ends by presenting some narratives composed after the recordings made with the group in the locations chosen by them. Keywords: Boca de Rua newspaper. Video-letter. Porto Alegre. Self-narrative. RESUMO O presente estudo compartilha o processo de conquista coletiva de uma vídeo-carta sobre a cidade de Porto Alegre, realizada com um grupo de diretores do jornal Boca de Rua, feito pelos moradores de rua de Porto Alegre. Destaca uma perspectiva que vê no narrador da cidade sua expressão e aposta que há compartilhamento e sociabilidade decorrentes dos fragmentos de narrativas produzidas pelas multiplicidades que a compõem. Como base, introduz alguns conceitos de narrativa e autonarrativa, assumindo, com base na teoria psicanalítica, que o “Eu” é excêntrico ao sujeito e que o “Eu” existe como uma construção parcial. Através dos autores W. Benjamin, P. Ricoeur, J-M. Gagnebin, J. Butler e J. Lacan, ressalta a importância de compor narrativas na assembleia de si e da cidade, criando conexões quando apropriado ou até legitimando o caráter fragmentário da narrativa. O artigo termina apresentando algumas narrativas compostas após as gravações feitas com o grupo nos locais escolhidos por eles. Palavras-chave: Jornal Boca de Rua. Vídeo-carta. Porto Alegre. Autonarrativa.